Ring closing metathesis approach to the indole alkaloid mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, R.; Kalkote, Uttam R. (Tetrahedron Letters, 2006)
An efficient utilisation of RCM leading to a convenient synthesis of a pentacyclic indole alkaloid is described. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: corynanthe type alkaloid; Dihydroxylation; mitralactonine; RCM; Swern oxidation

Rapid synthesis of the epi-biotin sulfone via tandem S,N-carbonyl migration/aza-michael/spirocyclization and haller-bauer reaction - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (ACS Omega, 2022)
A synthesis of 2-epi-biotin sulfone was accomplished from commercially available L-cysteine. The synthesis features an unprecedented tandem S,N-carbonyl migration/aza-Michael/spirocyclization reaction from an L-cysteine-derived enone with aq. ammonia, in which three new sigma bonds and two rings are formed. In addition, the synthesis includes a highly diastereoselective late-stage Haller-Bauer reaction of sulfone for direct introduction of the carbon side chain.

Revisiting classical pummerer cyclization reaction: a key strategy for the synthesis of (+/-)-quinagolide - Chavan, Subhash P.; Kawale, Sanket A.; Tripathi, Anupam; Kadam, Appasaheb L.; Gonnade, Rajesh G. (ChemistrySelect, 2022)
A formal synthesis of (+/-)-quinagolide using beta-alanine as a starting material has been achieved. Late stage intramolecular classical Pummerer reaction has been used as a key synthetic tool to construct octahydrobenzo[g]quinoline skeleton of quinagolide. Conjugative reduction of olefin, regioselective C-alkylation over O-alkylation of beta-ketoester followed by retro-Dieckmann/ Dieckmann reaction sequence has been used as a key reaction sequence to achieve prerequisite sulfoxide for the Pummerer reaction. While revisiting the classical Pummerer reaction, the one-pot sequential thionium ion induced cyclocarbamation followed by N-carbamate deprotection and Friedel-Crafts type Pummerer cyclization was observed as an important finding of the present work.
Keywords: Alkylation; Cyclocarbamation; Hyperprolactinemia; rearrangement; Thionium ion

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity